APPLICATIONS OF GENERALIZED ZORN’S LEMMA - Park, S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2022)
In the present article, by applying our 2013 Metatheorem and the Brøndsted-Jachymski Principle, we obtain various forms generalizations of Zorn’s Lemma and their applications. Such examples are our version of the Zermelo fixed point theorem, equivalent formulations of the Caristi fixed point theorem, and Jachymski’s 2003 theorem on equivalent conditions when fixed point sets are same to periodic point sets.